The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Verso, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

chapitre 3, « Les couvents comme expression organisée des aspirations des femmes » dans Profession: religieuse : un choix pour les Québécoises, 1840-1920 - Danylewycz, Marta; Linteau, Paul-André; Prentice, Alison; Westfall, William (Profession: religieuse : un choix pour les Québécoises, 1840-1920, 1988)
Marta Danylewycz s'intéresse à 2 communautés: les soeurs de Notre-Dame et de la Miséricorde, qui rassemblent près du cinquième de la population religieuse féminine au tournant du siècle.
Section: 246 pages : illustrations ; 22 cm
Keywords: 1800-1899; 1840-1849; 1850-1859; 1860-1869; 1870-1879; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; his4550; histoire; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis